Preparation method of anthracite-based soft and hard carbon composite negative electrode material of sodium ion battery
By using high carbon content anthracite and hard carbon machinery to prepare soft and hard carbon composite antelope materials, the problems of cumbersome operation and high cost in the prior art are solved, and the specific capacity and circulation performance of the material are significantly improved, and the preparation cost is reduced.
Patent Information
- Application Number
- CN202510034357.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing method of preparing negative electrode materials for soft and hard carbon composite sodium ion batteries is cumbersome and costly, which limits the large-scale application of materials.
High carbon content anthracite is used as a soft carbon carbon source to mix it with commercial hard carbon machinery to prepare composite materials, simplify production processes, improve negative electrode performance, and reduce costs.
The specific capacity and circulation performance of the material have been significantly improved. The preliminary specific capacity is 259-260mAh/g, the Coulomb efficiency in the first circle reaches 73%-75%, and the capacity retention rate after 500 cycles reaches 81%-84%, while the preparation cost is reduced by about 50%.
Smart Images

Figure CN119797329A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a soft and hard carbon composite negative electrode material. Background Art
[0002] As lithium resources become increasingly scarce, sodium-ion batteries have attracted widespread attention due to their abundant sodium resources and low cost. However, the negative electrode materials limit the practical application of sodium-ion batteries. At present, the mainstream negative electrode materials are carbon-based negative electrodes, which are divided into two amorphous carbon materials: hard carbon and soft carbon. Hard carbon is generally prepared by pyrolysis and high-temperature carbonization (>1000℃) with biomass or synthetic resin as precursors. It has the advantages of high sodium storage capacity (~300mAh / g) and low sodium storage voltage, but its precursor is expensive, the carbon yield is low, and the preparation process is complicated. Soft carbon is generally prepared by medium-temperature carbonization (<1200℃) with asphalt and petroleum coke as precursors. Its precursors are usually low in cost, have a more ordered structure, fewer defects and shorter interlayer spacing, but its specific capacity is often lower than that of hard carbon.
[0003] The use of soft and hard carbon composites can improve the capacity and rate performance of materials. For example, the soft and hard carbon composite method disclosed in the Chinese patent "A soft and hard carbon composite sodium ion battery negative electrode material and preparation method thereof" with application number 202111478021.0 requires acid pickling of the soft carbon precursor and high-temperature sintering of the hard carbon, which not only increases the process cost, but also makes the operation more complicated and the process more cumbersome due to the certain danger of acid treatment, which increases the cost and limits the large-scale application of soft and hard carbon composite materials. Summary of the invention
[0004] The present invention aims to solve the technical problems of complicated operation and high cost of the existing soft and hard carbon composite negative electrode material preparation method for sodium ion batteries, and provide a method for preparing anthracite-based soft and hard carbon composite negative electrode materials for sodium ion batteries. The present invention selects anthracite with high carbon content as a soft carbon carbon source, and mechanically mixes it with commercial hard carbon to prepare a composite material, aiming to simplify the production process, improve negative electrode performance, improve cycle stability, reduce costs, and achieve efficient resource utilization.
[0005] The method for preparing the anthracite-based soft and hard carbon composite negative electrode material for a sodium ion battery of the present invention is carried out according to the following steps:
[0006] 1. Anthracite is mechanically crushed, ball-milled, and sieved through a 200-mesh sieve to obtain anthracite powder with a particle size of less than 75 μm;
[0007] 2. The anthracite powder obtained in step 1 is placed in a tubular furnace, and under the protection of an inert gas, the temperature is raised to 1000-1400° C. and maintained for 2-3 hours for pyrolysis and carbonization, and then naturally cooled to room temperature with the furnace to obtain anthracite-based soft carbon material;
[0008] 3. Grind and mix the anthracite-based soft carbon material and the hard carbon material in a mass ratio of 1: (0.5-1) to uniformly mix the soft and hard carbons to obtain a soft and hard carbon composite negative electrode material.
[0009] Furthermore, the mass percentage of carbon in the anthracite in step 1 is greater than 80%, and the mass percentage of ash is less than 6%. The high carbon content provides a larger interlayer spacing and a more disordered structure after carbonization, and the low degree of graphitization is conducive to improving the electrical properties of the material.
[0010] Furthermore, the inert gas in step 2 is argon, nitrogen or helium.
[0011] Furthermore, the heating rate during the pyrolysis and carbonization in step 2 is 2 to 10° C. / min.
[0012] Furthermore, the grinding described in step three is manual grinding or ball milling.
[0013] The present invention uses anthracite soft carbon and commercial hard carbon to prepare negative electrode materials. By exploring the ratio of soft and hard carbon, the soft carbon is used to provide a conductive network, a stable sodium storage channel is formed during the sodium insertion process, and the structure is kept stable during the cycle; the hard carbon provides high-capacity sodium storage sites (such as pores and defects). The soft and hard carbon composite negative electrode material of the present invention has an initial specific capacity of 259-260 mAh / g, a first-cycle coulomb efficiency of 73%-75%, and a capacity retention rate of 81%-84% after 500 cycles. It has good comprehensive performance, and the preparation method is simple and the cost is low. It can be used in the field of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is the infrared spectrum of anthracite in step 1 of Example 1;
[0015] Figure 2 Thermogravimetric curve of anthracite in step 1 of Example 1;
[0016] Figure 3 The XRD spectra of the anthracite in step 1 of Example 1 and the anthracite-based soft carbon material obtained after carbonization in step 2;
[0017] Figure 4 XRD spectra of the anthracite-based soft carbon material obtained in step 2 of Example 1, the pure hard carbon in step 3, and the soft and hard carbon composite negative electrode material;
[0018] Figure 5 The Raman spectra of the anthracite-based soft carbon material obtained in step 2 of Example 1, the pure hard carbon in step 3, and the soft and hard carbon composite negative electrode material;
[0019] Figure 6 BET diagrams of the anthracite-based soft carbon material obtained in step 2 of Example 1, the pure hard carbon in step 3, and the soft and hard carbon composite negative electrode material;
[0020] Figure 7 The pore size distribution diagram of the anthracite-based soft carbon material obtained in step 2 of Example 1, the pure hard carbon in step 3, and the soft and hard carbon composite negative electrode material;
[0021] Figure 8 The scanning electron microscope photos of the soft and hard carbon composite negative electrode material prepared in Example 1 before and after cycling;
[0022] Fig. 9 Scanning electron microscope images of hard carbon before and after cycling. DETAILED DESCRIPTION
[0023] The beneficial effects of the present invention are verified by the following examples.
[0024] Example 1: The preparation method of the anthracite-based soft and hard carbon composite negative electrode material for sodium ion batteries of this embodiment is carried out according to the following steps:
[0025] 1. Mechanically crush the anthracite, ball mill it, and pass it through a 200-mesh sieve to obtain anthracite powder with a particle size of less than 75 μm;
[0026] 2. The anthracite powder obtained in step 1 is placed in a tubular furnace, and under the protection of nitrogen gas, the temperature is raised to 1300°C at a heating rate of 5°C / min and maintained for 3 hours for pyrolysis and carbonization, and then naturally cooled to room temperature with the furnace to obtain anthracite-based soft carbon material, which is recorded as SC;
[0027] 3. Put the anthracite-based soft carbon material (SC) and the hard carbon material (HC) in a mortar at a mass ratio of 1:0.6, and grind them manually for 30 minutes to evenly mix the soft and hard carbons to obtain a soft and hard carbon composite negative electrode material, recorded as SC-HC.
[0028] The composition of the anthracite in step 1 is shown in Table 1, and it is produced in Jincheng, Shanxi.
[0029] Table 1. Composition of anthracite
[0030] name Carbon content Moisture Ash Volatile Matter index 86.50% 0.31% 5.55% 7.64%
[0031] The hard carbon material described in step three is Type 2 Kuraray brand sodium battery negative electrode hard carbon, model Type 2.
[0032] Example 2: This example is different from Example 1 in that the anthracite-based soft carbon material and the hard carbon material in step 3 are in a mass ratio of 1:1 and are manually ground for 30 minutes to uniformly mix the soft and hard carbons to obtain a soft and hard carbon composite negative electrode material.
[0033] Comparative Example 1: This comparative example is different from Example 1 in that the mass ratio of the anthracite-based soft carbon material to the hard carbon material in step three is 1:0.43, and the other steps and parameters are the same as those in Example 1, to obtain a soft and hard carbon composite negative electrode material.
[0034] Comparative Example 2: This comparative example is different from Example 1 in that the mass ratio of the anthracite-based soft carbon material to the hard carbon material in step three is 1:1.5, and the other steps and parameters are the same as those in Example 1, to obtain a soft and hard carbon composite negative electrode material.
[0035] Figure 1 is the infrared spectrum of anthracite in step 1 of Example 1, from Figure 1 It can be seen that anthracite contains more hydrogen-containing functional groups, and the soft carbon generated by it as a carbon source has a smaller interlayer spacing, which makes it difficult for sodium ions to embed and detach, and the sodium storage capacity is low.
[0036] Figure 2 The thermogravimetric curve of anthracite in step 1 of Example 1 is shown in FIG. Figure 2 It can be seen that when the temperature rises to 300°C, the weight loss rate begins to increase and reaches a maximum at 440°C, which indicates that the raw coal cracks at this temperature and releases small molecular substances, including light hydrocarbons, CO, CO2 and other gases. The release of volatile components leads to the formation and expansion of pores, which increases its specific surface area. When the temperature rises to 800°C, the weight loss rate is greatly reduced. At this time, the aromatic structure of anthracite is further cross-linked and polymerized to form a larger carbon molecular network and a stable carbon skeleton structure, as well as a more ordered structure.
[0037] Figure 3 The XRD spectra of the anthracite in step 1 of Example 1 and the anthracite-based soft carbon material obtained after carbonization in step 2 are shown in FIG. Figure 3 It can be seen that the characteristic peak of anthracite (002) after high-temperature carbonization is sharper than that before carbonization, indicating that its crystallinity in the stacking direction is significantly increased, the order of the carbon layer is increased, and a highly graphitized structure with a small interlayer spacing is formed.
[0038] Figure 4 The XRD spectra of the anthracite-based soft carbon material obtained in step 2 of Example 1, the pure hard carbon in step 3, and the soft and hard carbon composite negative electrode material are shown in FIG. Figure 4 It can be seen that compared with the anthracite-based and soft carbon materials that are directly carbonized at high temperature, the (002) peak of the soft and hard carbon composite negative electrode material is significantly broadened and moves to a smaller angle, indicating that the interlayer spacing is enlarged and the order of the carbon microstructure is reduced. From the XRD results, it can be seen that the soft and hard carbon composite material presents a structure similar to that of hard carbon, and has more sodium storage sites accordingly.
[0039] Figure 5The Raman spectra of the anthracite-based soft carbon material obtained in step 2 of Example 1, the pure hard carbon in step 3, and the soft and hard carbon composite negative electrode material are shown in FIG. Figure 5 In the graphite matrix, the D peak represents the defect content and the G peak represents the degree of graphitization. The ratio of the two intensities is an important basis for judging the degree of disorder of the carbon matrix. Figure 5 As can be seen, the I of the soft and hard carbon composite negative electrode material D Than I G Compared with soft carbon, it has increased, which means that there are more defects in its carbon matrix, resulting in a less ordered carbon structure and correspondingly more sodium storage sites.
[0040] Figure 6 The BET diagrams of the anthracite-based soft carbon material obtained in step 2 of Example 1, the pure hard carbon in step 3, and the soft and hard carbon composite negative electrode material are shown in FIG. Figure 6 It can be seen that the nitrogen adsorption and desorption curves of the three materials are all type III adsorption isotherms, but the adsorption and desorption curve of hard carbon is not closed. It is speculated that this is caused by the particularity of the pore structure. The sample pore is similar to the structure of an ink bottle, with a smaller opening at the front and a larger opening at the back. It cannot be desorbed cleanly during desorption, which is also the reason why the initial coulomb efficiency of hard carbon is low. Sodium ions cannot be completely removed after embedding. The soft and hard carbon composite negative electrode material obtained by the composite of hard carbon and soft carbon blocks some pores of the hard carbon, which can effectively increase the initial coulomb efficiency.
[0041] Figure 7 The pore size distribution diagram of the anthracite-based soft carbon material obtained in step 2 of Example 1, the pure hard carbon in step 3, and the soft and hard carbon composite negative electrode material, from Figure 7 It can be seen that soft carbon has a larger pore volume and a wider pore size distribution, while hard carbon has a lower pore volume and a narrower pore size distribution, and a denser structure. Soft and hard carbon composites combine the properties of soft carbon and hard carbon, and the pore structure is between the two, maintaining a high electrolyte wettability and having appropriate structural stability.
[0042] The soft and hard carbon composite negative electrode materials prepared in Examples 1 and 2 and Comparative Examples 1 and 2 were used as active materials to prepare negative electrode plates for sodium ion batteries. The specific steps were as follows: the active material, conductive carbon black, and sodium carboxymethyl cellulose (CMC) were mixed in a mass ratio of 8:1:1, dissolved in water, and stirred for 24 hours to form a uniform viscous slurry. The slurry was applied to the surface of the copper foil, and evenly applied with a scraper with a thickness of 200 μm. It was then placed in a vacuum drying oven at 80°C and vacuum dried for 12 hours. It was then cut into discs with a diameter of 12 mm using a punching machine, and the loading amount of each pole plate was controlled to be 2 mg cm -2The prepared electrode was used as the negative electrode, the sodium metal disc with a diameter of 15.6 mm was used as the counter electrode, the glass fiber membrane was used as the diaphragm, the electrolyte was a dimethyl ether (DME) solution of NaPF6 with a concentration of 1 mol / L, the electrolyte dosage was 160 μL, and the assembled battery was at 1 Ag -1 The current density was 1Ag and the cycle was 500 cycles. -1 The initial specific capacity under current density, the first cycle coulombic efficiency and the capacity retention rate after 500 cycles are shown in Table 2. It can be seen from Table 2 that among the four soft and hard carbon composite materials with different proportions, the materials of Example 1 and Example 2 have excellent comprehensive performance, and have the advantages of high specific capacity and long charge and discharge cycle life.
[0043] Table 2 Cyclic performance of hard and soft carbon composites with different ratios and hard carbon and soft carbon
[0044]
[0045] Figure 8 The scanning electron microscope photos of the soft and hard carbon composite negative electrode material prepared in Example 1 before and after the cycle are shown in FIG. Figure 8 It can be seen that the original soft and hard carbon composite material combines the characteristics of hard carbon and soft carbon. The relatively fine soft carbon is attached to the surface of the large hard carbon. After 500 cycles, the composite structure of the soft and hard carbon composite material remains intact, showing high stability. Fig. 9 The scanning electron microscope pictures of hard carbon before and after cycling are shown in Figure 2. Fig. 9 It can be seen that the hard carbon has larger blocks before the cycle, but after 500 cycles, the structure collapses severely.
[0046] Comparative Example 3: The difference between this comparative example and Example 1 is that the anthracite composition described in step 1 is as shown in Table 3.
[0047] Table 3. Composition of anthracite
[0048] name Carbon content Moisture Ash Volatile Matter index 70.68% 1.53% 16.39% 11.4%
[0049] The other steps and parameters are the same as those in Example 1 to obtain a soft and hard carbon composite negative electrode material.
[0050] Comparative Example 4: The difference between this comparative example and Example 1 is that the anthracite composition described in step 1 is as shown in Table 4.
[0051] Table 4. Composition of anthracite
[0052] name Carbon content Moisture Ash Volatile Matter index 77.93% 0.54% 13.47% 8.06%
[0053] The other steps and parameters are the same as those in Example 1 to obtain a soft and hard carbon composite negative electrode material.
[0054] The soft and hard carbon composite negative electrode materials prepared in Comparative Examples 3 and 4 were used to prepare electrodes and assemble batteries in the same manner as the materials in Example 1, and the electrochemical performance tests were performed. The results are shown in Table 5.
[0055] Table 5 Cyclic performance of soft and hard carbon composites prepared from different anthracites
[0056]
[0057]
[0058] Compared with the soft and hard carbon composite negative electrode materials prepared in Example 1, the electrical properties of the soft and hard carbon composite negative electrode materials prepared in Comparative Examples 3 and 4 are lower. This is due to the different carbon contents in the anthracite raw materials. The anthracite in Example 1 has a high carbon content, and after carbonization, it has a larger interlayer spacing and a more disordered structure. At the same time, the degree of graphitization is low, which meets the physical and chemical property requirements of the negative electrode materials.
[0059] The present invention adopts a soft and hard carbon composite strategy to significantly improve the structural instability caused by volume expansion of hard carbon during the cycle, thereby effectively avoiding structural collapse in long cycles. At the same time, by mechanically mixing and doping anthracite-based soft carbon, the production cost is reduced by about 50%, and the process flow is simplified, solving the problem of poor cycle stability and high cost of hard carbon materials.
Claims
1. A method for preparing anthracite-based soft and hard carbon composite negative electrode material for sodium ion batteries, characterized in that The method proceeds as follows:
1. Anthracite is mechanically crushed, ball-milled, and sieved through a 200-mesh sieve to obtain anthracite powder with a particle size of less than 75 μm; 2. The anthracite powder obtained in step 1 is placed in a tubular furnace, and under the protection of an inert gas, the temperature is raised to 1000-1400° C. and maintained for 2-3 hours for pyrolysis and carbonization, and then naturally cooled to room temperature with the furnace to obtain anthracite-based soft carbon material; 3. Grind and mix the anthracite-based soft carbon material and the hard carbon material in a mass ratio of 1: (0.5-1) to uniformly mix the soft and hard carbons to obtain a soft and hard carbon composite negative electrode material.
2. The method for preparing an anthracite-based soft and hard carbon composite negative electrode material for a sodium ion battery according to claim 1, characterized in that: The mass percentage of carbon in the anthracite described in step 1 is greater than 80%, and the mass percentage of ash is less than 6%.
3. The method for preparing an anthracite-based soft and hard carbon composite negative electrode material for a sodium ion battery according to claim 1 or 2, characterized in that: The inert gas described in step 2 is argon, nitrogen or helium.
4. The method for preparing an anthracite-based soft and hard carbon composite negative electrode material for a sodium ion battery according to claim 1 or 2, characterized in that: The heating rate during the pyrolysis carbonization in step 2 is 2-10°C / min.
5. The method for preparing an anthracite-based soft and hard carbon composite negative electrode material for a sodium ion battery according to claim 1 or 2, characterized in that: The grinding described in step 3 is manual grinding or ball milling.
Citation Information
Patent Citations
Soft and hard carbon composite sodium ion battery negative electrode material and preparation method thereof
CN116230931A
Preparation method of hard carbon wrapped soft carbon taken as lithium ion battery anode material
CN108682804A
Carbon composite material for secondary battery, preparation method thereof and application thereof
CN109950548A
Soft and hard carbon composite material and preparation method and application thereof
CN114373908A
High-compaction sodium ion battery negative electrode material, negative electrode plate and sodium ion battery
CN115513440A
Cited By
Soft and hard carbon composite material and preparation method and application thereof
CN122224818A
Soft-hard carbon composite material and preparation method and application thereof
CN122224818B